Columbus Square - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, Trinidad, 2010)
This is a beautiful, historic, panoramic view of Columbus Square, corner of Independence Square and Duncan Street, Port of Spain. The monument to Christopher Columbus: navigator; explorer; colonizer, who encountered Trinidad in 1498 on his third voyage, stands here amid large trees, shrubs and grass. The iron statute at the top of the monument was a gift from Hippolyte Borde, an affluent local cacao planter and merchant. It is set in a large round fountain safeguarded by a high iron fence.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Monuments--Trinidad and Tobago; Memorials--Trinidad and Tobago; Statues--Trinidad and Tobago; Trees--Trinidad and Tobago; Buildings--Trinidad and Tobago; Fountains--Trinidad and Tobago; Columbus, Christopher